Effectiveness of Educational Intervention on Knowledge about Autism Spectrum Disorder among Primary School Teachers - Bhurtel, Bimala; Gurung, Bishnu; Sharma, Sharada (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Teacher’s knowledge on Autism Spectrum Disorder can play a key role in early identification of child with autism. This study aimed to find out the effectiveness of educational intervention on knowledge about autism spectrum disorder among primary school teachers.Methods: A pre-experimental one group pretest-posttest research design was used among 131 primary school teachers from selected private school of Pokhara Metropolitan City by using probability multistage random sampling technique. Validated pretested structured self-administered questionnaire was administered before and after educational intervention and collected data were analyzed using descriptive and inferential statistics (Paired t- test and chi square test) in SPSS Version 16 for window.Results: The findings of the study revealed that before educational intervention 60.8 percent teachers had inadequate knowledge level and 39.7 percent had moderate level of knowledge about autism spectrum disorders. Following the educational intervention knowledge level was increased where 79.4 percent had adequate knowledge and 20.6 percent had moderate level of knowledge about autism spectrum disorder. The mean knowledge scores before and after intervention were 19.48±3.837 and 32.83±2.96 respectively. Alternative hypothesis was accepted as the knowledge of teachers was significantly increased after the intervention.Conclusions: The study concludes that knowledge of teachers has increased after intervention hence educational intervention on autism spectrum disorder is effective. Therefore, it is advised to school’s authority to place greater focus on education initiatives in order to raise the level of understanding regarding autism spectrum disorder among teachers.